2004
DOI: 10.1007/s10692-005-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

X-ray diffraction method of determining the degree of crystallinity of cellulose materials of different anisotropy

Abstract: It is shown that the important change in the x-ray diffraction parameters in preparation of compact products from microcrystalline cellulose and ground cotton fibres by pressing is not due to the amorphous phase of cellulose. A method for determining the degree of crystallinity of cellulose in anisotropic materials using an external standard that ensures spherical scattering symmetry is substantiated. The applicability of the proposed approach for estimating the degree of crystallinity of cellulose fibres dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…4d ), the peaks at 16.4° from (101) plane reflection and 22.5° from (002) plane reflection were caused by the transverse arrangement of the crystallites in cellulose I. 24 Fig. 4e–h show X-ray diffraction patterns of MWCNT-cellulose, cellulose fibers, MWCNT/cellulose fibers and MWCNT-cellulose/cellulose fibers.…”
Section: Resultsmentioning
confidence: 94%
“…4d ), the peaks at 16.4° from (101) plane reflection and 22.5° from (002) plane reflection were caused by the transverse arrangement of the crystallites in cellulose I. 24 Fig. 4e–h show X-ray diffraction patterns of MWCNT-cellulose, cellulose fibers, MWCNT/cellulose fibers and MWCNT-cellulose/cellulose fibers.…”
Section: Resultsmentioning
confidence: 94%
“…2d ). Cellulose exhibited three peaks at 15.0° (101), 22.5° (002), and 34.5° (040) in X-ray diffraction (XRD) patterns, which are related to the transverse arrangement of microcrystals and the longitudinal structure of the polymer 24 . The crystalline structure still existed under 2 MPa but almost disappeared under 20 MPa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, pristine cellulose exhibits three characteristic peaks, as shown in Figure 2. The (101) and (002) reflections are caused by the transverse arrangement of the crystallites in cellulose I, while reflection (004) is related to the longitudinal structure of the polymer [25]. It is observed that when cellulose is hydrothermally treated at 210ºC, the resulting material exhibits a XRD pattern similar to that of pristine cellulose, indicating that the microcrystalline structure of the cellulose has been preserved.…”
Section: Characterization Methodsmentioning
confidence: 99%